Hyponatremia Is a Specific Marker of Perforation in Sigmoid Diverticulitis or Appendicitis in Patients Older Than 50 Years - S. A. Käser; R. Furler; D. C. Evequoz; C. A. Maurer (Gastroenterology Research and Practice)
Introduction. This study aimed to evaluate symptoms and signs, inflammation markers, electrolytes, and ECG signs of increased vagal tone as markers of colon perforation in sigmoid diverticulitis or appendicitis. Methods. The records of all patients older than fifty years (only these had routine ECG done) admitted to our emergency station between January 2008 and December 2010 with sigmoid diverticulitis (, diagnosed by computer tomography) or appendicitis (, diagnosed intraoperatively) were retrospectively evaluated. Pain score, heart rate, blood pressure, and body temperature were assessed at presentation. Before starting infusion therapy, blood was taken to do a blood count and to analyze CRP, the electrolytes, and creatinine levels. Then an ECG was done. Results. The perforation rate was 37% (). Body temperature, heart rate, sodium, CRP, and leukocytes correlated significantly with infectious colon perforation. However, only body temperature, CRP, and sodium correlated significantly with infectious colon perforation if compared by logistic regression analysis. The prevalence of hyponatremia (sodium level  mmol/L) was 29% in the group with infectious colon perforation and 16% in the group without (). Conclusion. Hyponatremia is a specific marker of infectious colon perforation in patients older than fifty years.